2018
DOI: 10.23925/1984-4840.2018v20i2a6
|View full text |Cite
|
Sign up to set email alerts
|

Percepção dos profissionais da estratégia saúde da família sobre as necessidades de saúde da população

Abstract: Objetivos: Identificar a percepção dos profissionais das equipes de saúde da família sobre as necessidades de saúde da população e analisar como essas necessidades são atendidas. Métodos: Pesquisa descritiva, qualitativa. Foram entrevistados 29 profissionais de saúde em 5 unidades de saúde da família, incluindo 6 profissionais de cada unidade, 1 de cada categoria profissional. A coleta de dados foi realizada por meio de entrevista oral e da aplicação de um formulário sociodemográfico. O conteúdo das entrevista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…With some participants in the present study, an understanding of health was observed as something that goes beyond the absence of disease. Being healthy is mentioned as not being sick or not feeling pain, but it is also referred to in an interconnected way as achieving quality of life, having a job, a family, bringing together aspects that encompass the health needs (18) of human beings; these needs are neglected in the context of HP's life.…”
Section: Discussionmentioning
confidence: 99%
“…With some participants in the present study, an understanding of health was observed as something that goes beyond the absence of disease. Being healthy is mentioned as not being sick or not feeling pain, but it is also referred to in an interconnected way as achieving quality of life, having a job, a family, bringing together aspects that encompass the health needs (18) of human beings; these needs are neglected in the context of HP's life.…”
Section: Discussionmentioning
confidence: 99%